Principles and applications of optogenetics in developmental biology - Krüger, Daniel; Izquierdo, Emiliano; Viswanathan, Ranjith; Hartmann, Jonas; Cartes, Cristina Pallares; Renzis, Stefano De (Development, 2019)
Skip to Next Section - The development of multicellular organisms is controlled by highly dynamic molecular and cellular processes organized in spatially restricted patterns. Recent advances in optogenetics are allowing protein function to be controlled with the precision of a pulse of laser light in vivo, providing a powerful new tool to perturb developmental processes at a wide range of spatiotemporal scales. In this Primer, we describe the most commonly used optogenetic tools, their application in developmental biology and in the nascent field of synthetic morphogenesis.